Universal weakly secure network coding - Silva, D.; Kschischang, F.R. (2009 IEEE Information Theory Workshop on Networking and Information Theory, 2009)
This paper considers the problem of secure network coding under the weak (and practically appealing) security requirements of Bhattad and Narayanan. Weak security allows communication at maximum rate while ensuring that only meaningless information is leaked to a wiretapper. Differently from the approach of Bhattad and Narayanan, which requires a joint design of the underlying network code and the outer security scheme, we propose a universal approach that is completely independent of the network code. In particular, the field size for linear network coding operations does not need to be enlarged. The scheme is also compatible with random network coding.